Functional Design in Rehabilitation: Modular Mechanisms for Ankle Complex - Francesco Aggogeri; Nicola Pellegrini; Riccardo Adamini (Applied Bionics and Biomechanics)
This paper is aimed at presenting an innovative ankle rehabilitation device based on a parallel mechanism. A functional analysis and design are described to obtain a device able to guarantee ankle movement while patient’s body remains stationary. Human ankle is a challenging context where a series of joints are highly integrated. The proposed rehabilitation device permits a patient with walking defects to improve his or her gait. The research focuses on plantar-flexion-dorsiflexion movement. The robust design starts from an accurate modelling of ankle movements during walking, assessing motion data from healthy individuals and patients. The kinematics analysis and functional evaluations lead the study and development of the articulated system. In particular, results of simulations support the effectiveness of the current design. A 3D prototype is presented highlighting that the ankle motion is successfully demonstrated.